A framework for studying the effects of offshore wind energy development on birds and bats in the Eastern United States - Williams, Kathryn A.; Gulka, Julia; Cook, Aonghais S. C. P.; Diehl, Robert H.; Farnsworth, Andrew; Goyert, Holly; Hein, Cris; Loring, Pamela; Mizrahi, David; Petersen, Ib Krag; Peterson, Trevor; Press, Kate McClellan; et al. (Frontiers in Marine Science, 2024)
Offshore wind energy development (OWED), while a key strategy for reducing carbon emissions, has potential negative effects to wildlife that should be examined to inform decision making and adaptive management as the industry expands. We present a conceptual framework to guide the long-term study of potential effects to birds and bats from OWED. This framework includes a focus on exposure and vulnerability as key determinants of risk. For birds and bats that are exposed to OWED, there are three main effects of interest that may impact survival and productivity: 1) collision mortality, 2) behavioral responses, including avoidance, displacement, and attraction, and 3) habitat-mediated effects to prey populations. If these OWED effects cause changes in survival and/or breeding success (e.g., fitness), they have the potential for population-level consequences, including changes in population size and structure. Understanding the influence of ecological drivers on exposure and effect parameters can help to disentangle the potential impacts of OWED from other stressors. We use this theoretical framework to summarize existing relevant knowledge and identify current priority research questions (n=22) for the eastern United States, where large-scale development of OWED is primarily in the planning and early construction phase. We also identify recommendations for study design and further prioritization of research topics.